Pretargeted PET Imaging with a TCO-Conjugated Anti-CD44v6 Chimeric mAb U36 and [Zr-89]Zr-DFO-PEG(5)-Tz - Lumen Dave; Vugts Danielle; Chomet Marion; Imlimthan Surachet; Sarparanta Mirkka; Vos Ricardo; Schreurs Maxime; Verlaan Mariska; Lang Pauline A; Hippeläinen Eero; Beaino Wissam; Windhorst Albert D; et al. (AMER CHEMICAL SOC, 2022)
The recent advances in the production of engineered antibodies have facilitated the development and application of tailored, target-specific antibodies. Positron emission tomography (PET) of these antibody-based drug candidates can help to better understand their in vivo behavior. In this study, we report an in vivo proof-ofconcept pretargeted immuno-PET study where we compare a pretargeting vs targeted approach using a new Zr-89-labeled tetrazine as a bio-orthogonal ligand in an inverse electron demand Diels-Alder (IEDDA) in vivo click reaction. A CD44v6-selective chimeric monoclonal U36 was selected as the targeting antibody because it has potential in immuno-PET imaging of head-and-neck squamous cell carcinoma (HNSCC). Zirconium-89 (t(1/2) = 78.41 h) was selected as the radionuclide of choice to be able to make a head-to-head comparison of the pretargeted and targeted approaches. [Zr-89]Zr-DFO-PEG S -Tz ([Zr-89]Zr-3) was synthesized and used in pretargeted PET imaging of HNSCC xenografts (VU-SCC-OE) at 24 and 48 h after administration of a trans-cyclooctene (TCO)-functionalized U36. The pretargeted approach resulted in lower absolute tumor uptake than the targeted approach (1.5 +/- 0.2 vs 17.1 +/- 3.0% ID/g at 72 h p.i. U36) but with comparable tumor-to-non-target tissue ratios and significantly lower absorbed doses. In conclusion, anti-CD44v6 monoclonal antibody U36 was successfully used for Zr-89-immuno-PET imaging of HNSCC xenograft tumors using both a targeted and pretargeted approach. The results not only support the utility of the pretargeted approach in immuno-PET imaging but also demonstrate the challenges in achieving optimal in vivo IEDDA reaction efficiencies in relation to antibody pharmacokinetics.